Eco-integrative territorial evocation by emerging new architectural eco-climatic style - Toumi, Labib; Kouzana, Lamia (Journal of Architecture and Urbanism, 2023)
In this research work, the interest is directed towards the evocation of innovative neo-architectural dynamics in the Tunisian south-east territory, through an eco-integrative approach and the production of new eco-climatic architectural styles, based on the natural and cultural wealth of the Tunisian territory, authentic and revolutionary, yet marginalized and restricted, giving rise to reactions to the question that arises: “Is the situation of the vernacular heritage in the Tunisian south-east the direct result of a lack of vernacular heritage potential knowledge lack or of a modernist, restricted and reductive architectural production?” A multi-scale architectural study of rustic heritage has been developed, including a morpho-metric study, the analysis of hygrothermal diagrams produced in situ as well as the measurement of temperature and humidity inside the spaces. Neotroglodytic architecture, allows to highlight the intelligible integration of this new architectural mode in the mineral and arid desert landscape and to detect the aspect of an ecological and sustainable architecture, offering a humble, comfortable and welcoming intra-spatial atmosphere. Otherwise, in southeastern Tunisia, diagnostics have shown that rural villages, partially occupied and exploited in an anarchic manner, are subject to real dangers that threaten their survival in the Saharan territory, considered a difficult area. Direct consequences of an unsuitable development process, these historic works are perceived as static in the face of a dynamic social process, which has led to the gradual increase in their abandonment rates. Similarly, a disfigurement of the rustic landscape results from poor adaptation due to the standardized reproduction of architectural styles “in search of modernity”. The new troglodyte modes present a versatile and capacitive cultural potential. The manifestation of cultural and spatial wealth thus emerges, with the lasting potential of constituting a vector of cultural transition for the territorial development of southeastern Tunisia.